2007
DOI: 10.1002/rra.1046
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a minimal adequate model to describe the biomass dynamics of river epilithon

Abstract: The present study sought to identify a minimal adequate model to describe the biomass dynamics of river epilithon, a functional indicator of river health. Identification of minimal adequate models is particularly necessary in river management, given the reduced number of variables authorities are willing to measure routinely. A model previously developed for epilithon dynamics in a pre-alpine river was applied to epilithon biomasses recorded in contrasting hydrological, trophic and light conditions at various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 57 publications
1
21
0
Order By: Relevance
“…The highest viable fractions (62.4%) were associated with intermediate discharges values between 48 and 80 m 3 s -1 , whereas for established low flow periods (DMF below 48 m 3 s -1 ) viable fractions were the lowest (41.9%), and for high flow periods (DMF above 80 m 3 s -1 ) viable fractions were intermediary (50.0%). A modelling approach demonstrated that hydrodynamics played a substantial role in biofilm biomass loss through a discharge-dependent detachment (Boulêtreau et al, 2008). This would indicate that following a disturbance and a biomass loss, biofilm bacterial communities tend to exhibit more important proportions of viable cells, likely active and growing (Werner et al, 2004), and involved in colonization processes.…”
Section: Discussionmentioning
confidence: 98%
“…The highest viable fractions (62.4%) were associated with intermediate discharges values between 48 and 80 m 3 s -1 , whereas for established low flow periods (DMF below 48 m 3 s -1 ) viable fractions were the lowest (41.9%), and for high flow periods (DMF above 80 m 3 s -1 ) viable fractions were intermediary (50.0%). A modelling approach demonstrated that hydrodynamics played a substantial role in biofilm biomass loss through a discharge-dependent detachment (Boulêtreau et al, 2008). This would indicate that following a disturbance and a biomass loss, biofilm bacterial communities tend to exhibit more important proportions of viable cells, likely active and growing (Werner et al, 2004), and involved in colonization processes.…”
Section: Discussionmentioning
confidence: 98%
“…Here we apply a model that was initially proposed for riverine peryphyton [ Uehlinger et al , 1996], and recently modified and tested in the field and in laboratory experiments, using different types of sediment substrate [ Labiod et al , 2007; Boulêtreau et al , 2006, 2008, 2010]. The model describes the evolution of the biofilm biomass X , measured as mg Chl‐a/m 2 : Term 1a is the biofilm growth according to a logistic law, where μ max is the maximum growth rate, and K s is the half‐saturation constant.…”
Section: Biofilm and Hydrodynamic Modelingmentioning
confidence: 99%
“…Models applied to long time-series suggested that, in natural conditions, epilithic biomass dynamics can roughly be considered as the result of equilibrium between phototrophic growth and discharge-dependant loss (UEHLINGER et al, 1996;BOULÊTREAU et al, 2006;BOULÊTREAU et al, 2008). Models that account for epilithic detachment only considered the effect of fluid forces, using current velocity or discharge as variables (HORNER et al, 1983;MOMO, 1995;UEHLINGER et al, 1996;SARAVIA et al, 1998).…”
Section: Introductionmentioning
confidence: 99%